2020
DOI: 10.1093/ageing/afz199
|View full text |Cite
|
Sign up to set email alerts
|

New horizons in iron deficiency anaemia in older adults

Abstract: Iron deficiency anaemia (IDA) is common in older adults and associated with a range of adverse outcomes. Differentiating iron deficiency from other causes of anaemia is important to ensure appropriate investigations and treatment. It is possible to make the diagnosis reliably using simple blood tests. Clinical evaluation and assessment are required to help determine the underlying cause and to initiate appropriate investigations. IDA in men and post-menopausal females is most commonly due to occult gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…IDA is a particular challenge in the elderly, 24 as this is the age group with the highest prevalence of IDA, and the highest risk of underlying GI cancer. 2 However, it is also the age group at highest risk of complications from invasive investigation or from subsequent surgery if required-and debatably the least to gain from intervention.…”
Section: Discussionmentioning
confidence: 99%
“…IDA is a particular challenge in the elderly, 24 as this is the age group with the highest prevalence of IDA, and the highest risk of underlying GI cancer. 2 However, it is also the age group at highest risk of complications from invasive investigation or from subsequent surgery if required-and debatably the least to gain from intervention.…”
Section: Discussionmentioning
confidence: 99%
“…TSAT was associated with worse functional capacity, while sTfR showed the highest performance as a predictor of functional capacity and also quality of life. sTfR is a biomarker that provides information on tissue iron demand and because it is insensitive to inflammation, it can detect anemia in patients with preexisting inflammatory states, which is particularly useful in distinguishing between anemia of chronic disease and anemias caused by lack of iron intake [33][34][35]. Previous studies of our group had already shown its ability to predict effort capacity and quality of life in patients with chronic HF globally [18], and this paper studies its impact and predictive value specifically in HFpEF compared with other iron metabolism biomarkers and explores differences along the HFpEF LVEF range.…”
Section: Functional Capacity Impairment and Quality Of Life Worseningmentioning
confidence: 99%
“…37 Others consider alternative iron indicators, such as serum transferrin receptor. 38 Nonetheless, no consensus has been reached to allow a standardized diagnosis of ID in OA. According to WHO cutoff thresholds, ID prevalence in older Mexican adults is low and may be underestimated when compared to the magnitude of anemia reported in this population.…”
Section: Discussionmentioning
confidence: 99%